Free Radical Scavenging Activity and Chemical Composition of Essential Oils from Chaerophyllum sativum Against Food-Related Microorganisms - Pourshamsian, Khalil; Montazeri, Naser; Barami, Zahra (Asian Journal of Chemistry, 2012)
Essential oil from aerial part of Chaerophyllum satyvum was obtained by hydrodistillation and analyzed by GC and GC-MS. The 95.9 % containing 42 compounds were identified. The main identified compounds were linalool (49.8 %), limonene (7.8 %), bicyclogermacrene (4.9 %) and a-santalol (4.6 %). The oxygenated monoterpens was main compounds of the oil. The antibacterial activity of the oil were tested by the disk diffusion method against three Gram-positive (Staphylococcus aureus, Bacillus cereus and Bacillus subtilis) and two Gram-negative (Escherichia coli, Candida albicans) bacteria with the 1-4 mg mL-1 and 1-0.5 mg mL-1 MIC, respectively.